The Effect of Family Environment and Internet Usage on Learning Motivation - Nugrahini, Rizki Widya; Margunani, Margunani (Fakultas Ekonomi, Universitas Negeri Semarang, 2015)
This research aims to identify the effect of family environment and the internet usage as learning source simultanly or partially on economics learning motivation. Population was Senior High School 5 students (IIS/Social Program) Semarang. 192 students were analyzed as sample. Data collecting method used questionnaire. While data analyzing used descriptive and double equal regression analysis. From the descriptive analysis, it was found that the learning motivation is high (62%), good family environment (61%), good internet usage as learning source (67%). Findings show that Â family environment and the internet usage as learning source simultanly give positive effect and significant to motivation in learning economics by 39.8%. Partially, family environment gives positive effect and significant to economics learning motivation by 17.2%, the internet usage as learning source gives positive effect and significant to economics learning motivation by 8.6%. It can be concluded that family environment and the internet usage as learning usage give positive effect and significant to economics learning motivation at Senior High School 5 Semarang simultanly and partially. Hence, it is suggested that family environment should be kept in good condition, the internet usage as learning media should be provided more optimal, family hopefully always keeps condusive, calm, comfortable and enjoyable condition, and the last, students should improve the intensity of accessing economics information through the internet.